Health care users’ rights: strategies for empowering community health agents and community - Gabriela Marcellino de Melo Lanzoni; Mônica Motta Lino; Mariana Cabral Schveitzer; Gelson Luiz de Albuquerque (Rev Rene)
The objective of this Convergent Care Research, based on the theoretical reference of Paulo Freire is to critically unveil the Letter of Health Care Users’ Rights and to create strategies for empowering the community through educational workshops. This study counted upon the participation of 470 Community Health Care Agents in the municipality of Florianópolis, SC, Brazil, organized into small discussion groups, which permitted a collective elaboration of five strategies, namely: disseminate the importance of the Health Care council through home visits, orientation plan for users concerning the “medication”, fixing posters about the first principle of the Letter in the Health Unit; disclose other health care support services; and the promotion of the Letter as an empowering instrument for the community. The interventions aimed to inspire the strengthening of actions between education and health with the objective of developing the health team, without requiring demands of socio-economic structure from the State.